Determination of the Intention to use Tablets in Higher Education Students: An Approach From the Theory of Planned Behavior - Figueroa-Ortega, Rafael (2025)
Objective. The objective of this research is to determine if the underlying factors of intention influence the use of tablets in Higher Education students, using the theory of planned behavior. Methodology. The research carried out was quantitative in nature, with a non-experimental cross-sectional cohort design. A convenience survey was applied to 330 students from an Engineering Faculty in northern Chile. The data obtained were tabulated, considering the attitude variables, subjective norms, perceived behavioral control and intention to use. The statistical procedure was carried out, considering the exploratory and confirmatory factor analysis and the structural equation, using the JASP software. Results. The main finding found allows us to interpret that attitude and perceived behavioral control present a positive relationship with the intention to use, while the subjective norm results in a negative and non-significant relationship with the intention to use tablets.